2010
DOI: 10.1158/1078-0432.ccr-10-0505
|View full text |Cite
|
Sign up to set email alerts
|

Tremelimumab in Combination with Exemestane in Patients with Advanced Breast Cancer and Treatment-Associated Modulation of Inducible Costimulator Expression on Patient T Cells

Abstract: Purpose: Tremelimumab is a fully human monoclonal antibody specific for CTL-associated antigen 4 (CTLA4) with single-agent activity in certain tumors but has not been evaluated in patients with breast cancer.Experimental Design: In a phase 1 study, 26 patients with advanced, hormone-responsive breast cancer received tremelimumab (3-10 mg/kg) every 28 days or every 90 days plus exemestane 25 mg daily. The objectives were to determine safety and the maximum tolerated dose (MTD) of tremelimumab with exemestane an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
165
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(173 citation statements)
references
References 26 publications
(29 reference statements)
7
165
1
Order By: Relevance
“…With regard to safety, it may be promising that plasma mAb was lower than what has been tolerated in humans trials. 33,34,49,50 Emphasizing the utility of local versus systemic CTLA4 blockage, it has been reported that combination of tumor-localized anti-CTLA4 scFv expression with systemic T-Reg depletion has a synergistic effect. 51 Further, the authors did not observe autoimmune reactions in a murine model when anti-CTLA-4 scFv Ab was expressed by the tumors and anti-CD25 Abs were administered intraperitoneally.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to safety, it may be promising that plasma mAb was lower than what has been tolerated in humans trials. 33,34,49,50 Emphasizing the utility of local versus systemic CTLA4 blockage, it has been reported that combination of tumor-localized anti-CTLA4 scFv expression with systemic T-Reg depletion has a synergistic effect. 51 Further, the authors did not observe autoimmune reactions in a murine model when anti-CTLA-4 scFv Ab was expressed by the tumors and anti-CD25 Abs were administered intraperitoneally.…”
Section: Discussionmentioning
confidence: 99%
“…Also, inducible costimulator (ICOS) a member of the immunoglobulin gene family, seems to be involved. In some studies a correlation between increased frequency of circulating CD4 + ICOShigh T cells and Overall Survival has been shown (Chen et al, 2009;Vonderheide et al, 2010;Charton et al, 2010). Promising biomarkers also appear to be increases in CD54RO and HLA-DR on circulating CD4 + and CD8 + T cells (Comin-Anduix et al, 2008), poly-epitope antigen specific immune responses (Yuan et al, 2008) and degree of intratumoural Treg infiltration (Ribas et al, 2009).…”
Section: Biomarker Strategiesmentioning
confidence: 99%
“…No signiicant clinical response was observed by treatment although 42% of patients achieved stable disease for more than 3 months [55]. The anti-CTLA4 mAb ipilimumab is now being tested in patients with earlier stage or lower tumor burden.…”
Section: Immunotherapy In Breast Cancermentioning
confidence: 99%